The complete letters of Henry James, 1880-1883. Volume 2 - James, Henry; Anesko, Michael; Zacharias, Greg W., 1958-; Sommer, Katie (Lincoln : University of Nebraska Press, 2017)
The Complete Letter of Henry James, 1880-1883, volume 2, contains 178 letters, of which 98 are published for the first time.
September 11 To Moncure Daniel Conway -- September 14 To William Dean Howells -- October 7 To Elizabeth Boott -- October 15 To William James -- October 15 To William Dean Howells -- October 16 To Alice Howe Gibbens James -- October 17 To Grace Norton -- [18-28 October] To James Ripley Osgood -- October 28 To Henrietta Reubell -- November 8 To James Ripley Osgood -- November 12 To Isabella Stewart Gardner -- November 13 To Sir John Forbes Clark -- November 22 To Charles Hallam Elton Brookfield -- November 22 To William Henry Huntington -- November 26 To John Milton Hay -- November 27 To William Dean Howells -- [November 30] To Theodore E. Child -- November 30 To William Dean Howells -- December 1 To Elizabeth Eberstadt Lewis -- December 5 To John Milton Hay -- December 5 To Theodore E. Child -- December 5 To Henrietta Reubell -- December 6 To Robertson James -- December 8 To Elizabeth Eberstadt Lewis -- December 10 To Edmund Gosse -- [December 11] To Elizabeth Eberstadt Lewis -- [December 24, 1882-August 12, 1883] To George Abbot James -- [December 24 or 31] To Charles Eliot Norton -- December 26, 27 To William James -- December 26 To Frederick Macmillan -- [December 28, 1882, or January 4 or 11, 1883] To Elizabeth Cabot Lodge James -- December 28, 29 To William James -- December 29 To Gertrude Bloede -- December 30 To Robertson James -- December 30 To Grace Norton -- December 30 To Lady Louisa Erskine Wolseley -- 1883 -- January 1 To William James -- January 1 To James Ripley Osgood -- Biographical Register -- General Editors' Note -- Works Cited -- Index.
Vendor-supplied metadata.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: James, Henry, -- 1843-1916 -- Correspondence; James, Henry, -- 1843-1916; Authors, American -- 19th century -- Correspondence; Authors, American -- 20th century -- Correspondence; Écrivains américains -- 19e siècle -- Correspondance; Écrivains américains -- 20e siècle -- Correspondance; LITERARY COLLECTIONS -- Letters; Authors, American; 1800-1999; Personal correspondence